Glycemic control and hunger during recovery from high- and moderate-intensity Nordic skiing in well-trained skiers - Braun, W. A. (The Journal of Sports Medicine and Physical Fitness, 2016)
ABSTRACT: BACKGROUND: The aim of this paper was to study the effects of Nordic ski training on post-exercise blood glucose (BG) regulation. METHODS: Twenty-one (male N.=10; female N.=11) competitive college Nordic skiers (age 19.14 +/- 1.3 yrs; body fat percentage 14.9 +/- 6.2) completed two ski training conditions (high intensity [HI] and easy volume [MOD]) and one resting control (CON) condition on separate days. At rest on the control day and upon completion of ski training, a 75 g oral glucose tolerance test (OGTT) was administered. BG was measured prior to the OGTT and at 20-minute intervals for 80 minutes of passive rest. Hunger was assessed prior to the OGTT and at 40 and 80 minutes of rest via Visual Analog Scale. Data were analyzed using a two-way ANOVA with repeated measures and one-way ANOVA (SPSS v. 19). RESULTS: Significant time effects were present for BG. BG area under the curve (AUC) was significantly smaller (P<0.05) following HI (8825 +/- 149 arbitrary units [a.u.]) vs. CON (9493 +/- 168 a.u.), but not different from MOD (9087 +/- 227 a.u.). MOD AUC tended to be smaller than CON (P=0.064). Mean CON hunger was lower than MOD (P<0.05) and tended to be lower than HI (P=0.064). CONCLUSIONS: High-intensity Nordic skiing appears to enhance glycemic control when provided with an OGTT following acute exercise. The role that active muscle volume plays in this response should be investigated.